PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK SUHU DAN KALOR DI KELAS X SEMESTER II SMA NEGERI 1 DELITUA - Almira Novriyanti; Derlina . (INPAFI (Inovasi Pembelajaran Fisika), 2014)
ABSTRACT This study aims to determine the effect of problem-based learning model on student learning outcomes in the subject matter of temperature and heat in the second half of class X SMA Negeri 1 Delitua. This research is quasi-experimental. The study population was all students of class X SMA Negeri 1 Delitua which consists of 10 classes then performed by means of cluster sampling random sampling. The instrument used to determine student learning outcomes are achievement test in the form of essay tests totaling 10 questions. The results were obtained an average value of the experimental class pretest 31,90 and control class 30,48 . Once the data pretest is normal and homogeneous difference test second grade values ​​obtained that both classes have the same initial ability. Then given a different treatment, the experimental class with a problem-based learning model and grade control with conventional models. From the observation of student activity conducted by the observer in experimental class found that the average value of three times the activity of students meeting with a fairly active category. The average value of 71,63 posttest experimental class and control class 67,48. Once the data posttest is normal and homogeneous difference test second grade values ​​obtained that there is a difference due to the influence model of problem-based learning on learning outcomes of students in the subject matter of temperature and heat in class X SMA Negeri 1 Delitua. Key Words : problem-based learning model, activity, learning outcomes